Memorandum of Understanding between the BRAC University of Dhaka, Bangladesh And Bloomsburg University of Pennsylvania, USA (2009) - BRAC University; Bloomsburg University (BRAC University and Bloomsburg University, 2013)
This Memorandum of Understanding is made between BRAC University of Dhaka, Bangladesh (hereinafter called "BRAC UNIVERSITY") and Bloomsburg University of Pennsylvania, USA (hereinafter called "Bloomsburg University").